KAJIAN RELASI GENDER DALAM PENGHIDUPAN KELUARGA NELAYAN DI KAMPUNG TANJUNG BATU KECAMATAN PULAU DERAWAN KABUPATEN BERAU - Soni Suhendra; Erwiantono; Qoriah Saleha (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
The purposes of this riset was to know the perceptions of fishermens’s family in Tanjung Batu village about gender relations concept, the division of working system, revenue contribution, the making decisions system, working time duration, and also to able to know the system of access and control of marine and fisheries resourcea and social economic resources in fishermen’s family in Tanjung Batu village. The sampling method that has been used the purposive sampling, with 25 fishermen’s family (each family composed of husband and wife) that have operated 5 dominant fishing gear such as pukat, pancing, bubu, bagan tancap and bagan perahu. The research was conducted since October 2017 to June 2018. The analysis method of this data was description method which is based of crossing tabulation with qualitative approach. The result has shown that 96% perception in fishermen’s family related to gender relations concept is “women (wives) and men (husbands) realize that gender does not have to be a problem in managing the family or in the working field, but actually can be supported each other”. The system of making decision and divison of working within domestic activities is usualy dominated by the wives, while the things that are related to public activites is often dominated by both of husbands and wives. Revenue contribution 74% was come from husbands and 26% from wives. Working time duration of wives productive time were 6,6 hours/day (27,6%) and husbands were 11 hours/day (45,7%).The access and control of of marine and fisheries resources and social economic resources were often dominated by both of husbands and wives.